Leading the BSP in the pandemic - Diokno, Benjamin E.; Patawaran, AA (Intramuros, Manila Manila Bullettin Publishing Corp., 2024)
On 17 March 2020, with Benjamin E. Diokno barely into his first year as governor of Bangko Sentral ng Pilipinas (BSP), news about Covid-19 erupted. A lockdown was imposed all over Luzon and later the rest of the country.

It was gloom and doom all over. Mobility was restricted. Social distancing was the rule. Economic activity contracted. Many jobs were lost. “It was worse than war,” recalls Diokno. “The virus was invisible, it was all over, and potentially lethal.”

At the BSP, Diokno was told that, based on existing policy involving national emergencies, the BSP must close.

The governor was baffled. “I did not understand why the BSP must stop doing its job in a crisis,” he recounts. “I impressed upon our people: ‘You are essential workers, much like the nurses, doctors… It is your responsibility to keep the financial system open and the economy working.’”

As former budget chief under three administrations, Diokno recognized the enormous problem faced by the national government: Revenues would plummet as the economy came to a halt, spending needs would rise as medical expenses soared and welfare grants to affected citizens multiplied. The national government would need monumental assistance.

In brief, under Diokno as governor, the BSP remained open and the economy, despite a health crisis that unsettled the whole world, continued to work.

This book details how Diokno and the BSP, along with others in the public and private sectors, did it.
Monetary policy responses during the pandemic – Financial sector policy responses during the pandemic – Promoting financial inclusion – Enhancing consumer protection – Agri-agra law revisited – Strengthening the rural banking system – Setting ceilings on credit card finance charges – Enhancing digital transformation – Accelerating payments and currency management reforms – Improving the organizational structure and manpower complement – Reforming the procurement system – Institutionalizing research and research collaboration – Declaring massive dividends and adopting the cash-based budgeting system – BSP’s own Build, Build, Build Program – Working with Congress.
Includes bibliographical references.
Keywords: Bangko Sentral ng Pilipinas -- Management; Banks and banking, Central -- Philippines -- Decision making; Monetary policy -- Philippines; COVID-19 Pandemic, 2020 -- Economic aspects -- Philippines; Bankers -- Philippines .; Philippines -- Economic conditions -- 1986-.